Pengaruh Tingkat Pembiayaan Mudharabah, Pembiayaan Murabahah Dan Pembiayaan Musyarakah Terhadap Non Performing Financing (NPF) Pada Bank Umum Syariah Di Indonesia Tahun 2017-2022 - Hera Yanti; Maman Darmansyah (Yayasan Literasi Ilmiah Indonesia, 2023)
Banking operational activities in distribution, the bank gets benefits in the form of revenue sharing which can later increase the bank's growth, but in non-performing financing the increase in financing, the greater the risk faced, meaning that the higher the amount of financing, the possibility of non-performing financing will also increase. This study aims to analyze the effect of NPF growth on Islamic Commercial Banks in Indonesia using data for the 2017-2022 period. Performance measurement of Islamic banking in determining NPF. This study uses Mudharabah financing, Murabahah financing and Musyarakah financing based on data for the 2017-2022 period the number of samples used is 96. This study aims to examine the effect of the level of Mudharabah financing, Murabahah financing, and Musyarakah financing on NPF (Non Performing Financing) at Commercial Banks Sharia in Indonesia. To achieve this goal, researchers use the Multiple Linear Regression method. The partial test results of this study indicate that the level of Mudharabah financing has a negative effect on NPF at Islamic Commercial Banks in Indonesia. On the other hand, Murabahah and Musyarakah financing has no effect on NPF at Islamic Commercial Banks in Indonesia. Keywords: NPF, Mudharabah financing, Murabahah financing, Musyarakah financing.